The effect of azolla (azolla pinnata) extract on the growth and yield of sweet corn under reduced nitrogen fertilization practice - Mok Sam Lum; Nurul Fadhilah binti Aldam; Clament Fui Seung Chin (Sarhad Journal of Agriculture, 2024)
Sweet corn (Zea mays L. var. saccharata) is an important palatable grain grown for human consumption, for both fresh and processed foods. In this study, efficacy of Azolla pinnata aqueous extract on the growth and yield of sweet corn through foliar application was evaluated. Independent variables were application rates of urea (120, 110, 100, 90, 80, and 0 kg ha-1) and aqueous Azolla extract (AE i.e. 0, 10, 20, 30, 40, and 100%, v/v). Common variables were 60 kg/ha triple superphosphate (TSP), 90 kg/ha muriate of potash (MOP), and watering. The dependent variables were growth and yield parameters of sweet corn. Oneway ANOVA was used for analysis, where significant differences between treatments were determined using the Least Significant Difference (LSD) Test (SAS 9.4 software). Results revealed significant differences (p <0.05) in sweet corn that received AE foliar spray in plant height (p = 0.0098), stem diameter (p = 0.0419), leaf area (p = 0.0364), cob length (p = 0.0077), and number of grains per cob (p = 0.0207) compared to the control plant received an optimal rate of 120 kg ha-1 urea without AE. No significant differences were recorded for chlorophyll content, cob fresh weight, and weight of 100 grains. It is found that sweet corn received high N with the lowest AE (110 kg ha-1 urea + 10% AE) enhanced vegetative growth in plant height, stem diameter, leaf area, cob length, and grain yield. In sum, AE of Azolla is a potential and environmentally friendly organic fertilizer that is easy to grow, prepare, and apply by growers, in compensation for the reduction of 10 kg ha-1 urea used in sweet corn cultivation.